Some Topological Properties of Charming Spaces (Communications in Mathematical Research, 2019)
In this paper, we mainly discuss the class of charming spaces. First, we show that there exists a charming space such that the Tychonoff product is not a charming space. Then we discuss some properties of charming spaces and give some characterizations of some class of charming spaces. Finally, we show that the Suslin number of an arbitrary charming rectifiable space is countable.
Keywords: charming space; ($i; j$)-structured space; Lindelöf Σ-space; Suslin number; rectifiable space